Republic of Mozambique : Technical Assistance Report-Inflation Targeting and Model-based Monetary Policy Analysis. (IMF Staff Country Reports; Country Report, 2021)
The purpose of the mission was to improve the understanding of the conduct of monetary policy in an inflation targeting (IT) central bank. During the September visit, the mission provided capacity building through daily morning seminars, giving an introduction to modern theory of monetary policy in small-open economies, and by performing monetary policy analyses based on BM's quarterly projection model (QPM) in the afternoons.